2019
DOI: 10.4317/medoral.23035
|View full text |Cite
|
Sign up to set email alerts
|

Clinical repercussions and epidemiological considerations of supernumerary canines: A 26 case series

Abstract: BackgroundTo establish the prevalence of supernumerary canines (SNC) in a sector of the population of Madrid (Spain), as well possible complications associated with this unusual developmental variation.Material and MethodsThis observational study was performed between 2005 and 2017, among 21,615 patients seeking dental treatment at the Faculty of Dentistry, Complutense University of Madrid (Spain), and at the Virgen de la Paloma Hospital, Madrid (Spain); 22 patients with 26 SNCs were diagnosed. These 22 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…In a study on clinical repercussions of supernumerary canines, almost 70% of supernumerary teeth found were impacted, and half of them also caused the impaction of the permanent canines. Authors suggest that early diagnosis is mandatory to prevent complications and to reduce the treatment need or the complexity of the case [ 51 ]. This agrees with other studies that state that anomalies in the deciduous dentition also determine anomalies in the permanent one [ 36 , 37 ].…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…In a study on clinical repercussions of supernumerary canines, almost 70% of supernumerary teeth found were impacted, and half of them also caused the impaction of the permanent canines. Authors suggest that early diagnosis is mandatory to prevent complications and to reduce the treatment need or the complexity of the case [ 51 ]. This agrees with other studies that state that anomalies in the deciduous dentition also determine anomalies in the permanent one [ 36 , 37 ].…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…P-SNCs are normally rare (0.04 -4.17%), [14,47] finding d-SNCs are even rarer. [15,48,49] A majority of SNCs occur in the maxilla unilaterally with supplemental morphology. [14,47,50] The SNCs are associated with a high percentage of mechanical-obstructive pathology such as impaction, delayed eruption, ectopic eruption, root resorption of adjacent teeth, fusion with adjacent teeth, crowding, and cystic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study reported them to have almost an equal percentage of supplemental and conical shapes [26]. Cortés-Bretón-Brinkmann et al [46] reported that of the 26 supernumeraries in their study, 14 (53.85%) had supplemental morphology and 12 (46.15%) heteromorphic morphology.…”
Section: Supernumerary Teeth In the Anterior Regionmentioning
confidence: 92%
“…Supernumerary canines are extremely rare. Among 21,615 Spanish patients, 22 with 26 supernumerary canines were diagnosed presenting a prevalence of 0.10% [46]. In a study conducted among 5,200 Turkish patients, only one was diagnosed with a supernumerary canine [26].…”
Section: Supernumerary Teeth In the Anterior Regionmentioning
confidence: 99%
See 1 more Smart Citation